Bone mass regulation of leptin and postmenopausal osteoporosis with obesity - Legiran, Siswo (CIC Edizioni Internazionali, 2012)
BACKGROUND: Leptin has been known to play a role in weight regulation through food intake and energy expenditure. Leptin also has an important role in bone metabolism. The role of leptin is determined by leptin receptors, either central or peripheral to the bones. DESIGN: We discuss the role of leptin on bone and molecular genetics of osteoporosis in postmenopausal obese women. RESULTS: The role of leptin in bone preserves bone mineral density (BMD) through increased OPG levels leading to bind RANKL, resulting in reducing osteoclast activity. The estrogen role on bone is also mediated by RANKL and OPG. In postmenopausal women who have estrogen deficiency, it increases the rate of RANKL, which increases osteoclastogenesis. Obese individuals who have a high level of leptin will be effected by bone protection. CONCLUSION: There are similarities in the mechanism between estrogen and leptin in influencing the process of bone remodeling. It may be considered that the role of estrogen can be replaced by leptin. Molecular genetic aspects that play a role in bone remodeling, such as leptin, leptin receptors, cytokines (e.g. RANK, RANKL, and OPG), require further study to be useful, especially regarding osteoporosis therapy based on genetic analysis.